Two new sesquiterpene lactone glycosides from Cnicus benedictus. Issue 19 (2nd October 2017) - Peng, Ying; Jian, Yuqing; Zulfiqar, Ali; Li, Bin; Zhang, Kaiqiang; Long, Fei; Peng, Caiyun; Cai, Xiong; Khan, Ikhlas A.; Wang, Wei
Abstract: Two new sesquiterpene lactone glycosides, namely melitensin 15- O - β -D-glucoside (1 ) and 11 β, 13-dihydrosalonitenolide 15- O - β -D-glucoside (2 ), along with eight known compounds (3–10 ) were isolated from the aerial part of Cnicus benedictus L. Their structures were elucidated from analyses of extensive spectroscopic data. Compounds1–6 all possessed an α -methyl- γ -lactone moiety. Moreover, compound5 exhibited moderate activity against the growth of Aspergillus fumigatus, with IC50 values of 17.67 μg mL −1 . Abstract :